Photodynamic Inactivation of Porphyromonas gingivalis utilizing Radachlorin and Toluidine Blue O as Photosensitizers: An In Vitro Study - Moslemi, Neda; Rouzmeh, Nina; Shakerynia, Fatemeh; Bahador, Abbas; Soleiman-zadehazar, Pardis; Kharrazifard, MohamadJavad; Paknejad, Mojgan; Fekrazad, Reza (Journal of Lasers in Medical Sciences, 2018)
Introduction: Porphyromonas gingivalis is one of the major pathogens in the development and progression of periodontal disease. Antimicrobial photodynamic therapy (aPDT) is a new approach which is sorted in non-invasive phototherapy for bacterial elimination. This in vitro study was conducted to compare photodynamic inactivation using Radachlorin and Toluidine blue O (TBO) as photosensitizers on P. gingivalis. Methods: Bacterial suspensions (200 μL) of P. gingivalis were exposed to either TBO with concentration of 0.1 mg/mL associated with portable light-emitting diode (LED) device (peak wavelength: 630 nm, output intensity: 2.000 mW/cm2, tip diameter: 6.2 mm) or 0.1% Radachlorin® and laser irradiation (InGaAlP, Peak wavelength: 662±0.1% nm, output power: 2.5 W, energy density: 6 J/cm2, fiber diameter: 2 mm). Those in control groups were subjected to laser irradiation or LED alone, Radachlorin® or TBO alone, and one group received neither photosensitizer nor light irradiation. Then counting of colony forming units (CFU) was performed to determine the bactericidal effects in each subgroup. Results: LED-based aPDT reduced the colony count of P. gingivalis more than that of TBO (P < 0.001) or LED group (P = 0.957). Also, laser-based aPDT had a great reduction in colony count of P. gingivalis in comparison with Radachlorin® (P < 0.001) or laser irradiation alone (P = 0.28). In addition, the colony count reduction of laser-based aPDT was significantly more than LED-based aPDT (P < 0.05). Conclusion: Considering the results of this study, the viability of P. gingivalis was more affected by the combination of laser and Radachlorin® 0.1% in comparison with LED and TBO 0.1%